The effects of emotional distractors on the performance of cognitive tasks - Gaeta, Giuliano (2018)
Emotional stimuli can influence the performance of a cognitive task when presented in conjunction with it, although irrelevant to its completion. However, several criticalities and relevant gaps in the current literature on emotional distraction can be detected, and the present work aims to contribute to a better definition and understanding of the electrophysiological and, above all, behavioural correlates of the interaction between the two domains of cognition and emotion. Following a brief overview of this manuscript, chapters 2-3 provide background information on emotions, their properties and their interaction with cognitive processes. Chapters 4-8 report five experiments conducted to study this interaction, all employing behavioural and self-reported measures, and the first comprising electroencephalographic recordings. Further, for the first time, we analysed how individual approach/avoidance dominance can be associated with the effects of emotional distractors on task performance. After studying the effects of the valence of the distractors and the effects of task difficulty, we analysed how different types of distractors (words and pictures) affected the completion of emotionally salient and neutral tasks. A general discussion commenting on the results obtained in all the studies closes this work. The framework delineated here is absent in the current literature. The unicity and relevance of the work proposed lies particularly in the methodological approach toward the study of emotional distraction, which can in principle help to unveil the neural and behavioural mechanisms of physiological interaction between emotion and cognition dimensions.